Desenvolvimento de protocolo de regeneração e indução in vitro e in vivo de autotetraplóides em mamoneira (Ricinus communis L.) - Silva, Pollyana Karla da (2010)
The castor bean plant (Ricinus communis L.) is a diploid specie that have chromosomes in number of 2n=2x=20. The castor bean plantlets are hard to be in vitro regenerated because its recalcitrance requires a good in vitro regeneration protocol. The aim of this work was to develop an in vitro and ex vitro polyploidy induction protocol for castor bean (Ricinus communis). Experiments were conducted in Tissue Culture Laboratory of Agricultural Sciences Center from Universidade Federal da Paraíba, Campus II, Areia – PB. Castor bean seeds of variety E1P17 A/B were utilized. In the 1 experiment, the explants had been inoculated along eight different nutritive mediums of Margara (N5Ca, N30Ca, N30K, N15K, N15Ca, N45K, N5K, N30NH4), in the 2 experiment, in médium N5Ca with 6 sucrose concentrations (0, 1,0, 2,0, 3,0, 4,0 e 5,0%,), in the 3 experiment, the plantlets had being added in Trifluralin solutions with 0, 5, 10, 15, 20, 25 μM concentrations for 16 hours, and in the 4 experiment was applied a Trifluralin solution (10 M), which treatments were T0 (no application), T1 (only one application), T2 (two applications) e T3 (three applications) over the apical meristem of the plantlets. Therefore, based on these experiments results, the conclusion is that it is possible to propagate in vitro castor bean plant utilizing N5Ca medium of Margara and sucrose by 3% had shown the best morphogenetic result. For in vitro induction of the castor bean polyploidy, might be tested less than 10 M concentrations or reduce exposition time for 16 hours; and morphological variations are important at polyploidy plants identification in castor bean plants.